(untitled) (Itinera, 2015)
In this essay it will be argued that Aristotle took a clear position in the modern debate about what the so-called “sudden” is. Even though rather rarely, the speculative problem is expounded by the Stagirite especially in Rhetoric, using the strange word αὐτοκάβδαλος, which will be analysed for the first time. Moreover, the very reconstruction of the question is connected to the development of the epicurean doctrine of clinamen as sudden atomic motion.